Simulation Research of Tooth Break Faults of Planetary Gearboxes Considering the Transmission Path - Sun Mingshuai; Wang Liming; Nie Yanyan (Jixie chuandong)
Tooth break is a common fault which always occurs in the planetary gearboxes, and when it occurs, due to the influence of transmission path, the vibration signal collected by the sensor becomes complicated, which brings difficulties to fault diagnosis. Thus, in order to study the influence of transmission path on spectrum structure of planetary gearboxes with tooth break fault, the rigid-flexible coupling models with no fault, sun gear tooth break fault, planet gear tooth break fault and ring gear tooth break fault of planetary gearboxes are established on Adams, and the vibration signals of the box body are extracted and analyzed by simulation. The simulation results show that: in the time-domain, the change of the path will have an obvious amplitude modulation on the vibration signal which is measured at a fixed point of the box. What's more, in the spectrum diagram, the two sides of the meshing frequency will also produce side bands composed of different frequencies.This study can provide basis and reference for fault diagnosis of planetary gearboxes in the future.